Is there any correlation between muscle fatigue and serum lactate dehydrogenase levels in prediabetic individuals? - Charu Mishra; Vinita Ailani; Deepak Saxena; Yogesh Kumar Yadav; Suresh Singh; Vijay Kumar; Ranjan Kumar Dixit (Open Exploration Publishing Inc., 2022)
Aim: Lactate dehydrogenase (LDH) is an enzyme that acts as a catalyst in the conversion of lactate to pyruvate which is abundantly found in liver, kidney, heart and muscles. Previous studies have all shown a strong positive correlation between muscle fatigue and increased serum LDH levels with type 2 diabetes mellitus but no study has actually assessed the same for prediabetes. The basic objective of this study, thus, is to find out the correlation between muscle fatigue and serum LDH levels in prediabetic individuals. Methods: A cross-sectional study was conducted in adults between 24-60 years old who were classified as prediabetic individuals as per norms established by American Diabetes Association. A total of 100 prediabetic individuals were selected for the study. Fatigability was calculated as a function of work done by the pleximeter finger of the dominant hand using Mosso's ergograph. The study was conducted at Rajarshi Dashrath Autonomous State Medical College, Ayodhya. Results: Out of 100 prediabetic participants, 50% were males with a mean age of 44.14 ± 10.91 years and remaining 50% were females with a mean age of 41.12 ± 11.5 years. Overall, the average work done by the participants was 2.9 ± 1.2 weight lifted•total distance moved (kg•m) with an average serum LDH level of 323.84 ± 26.82 unit/litre (U/L). Conclusions: This study aimed at assessing the correlation between muscle fatigue and serum LDH levels in prediabetic individuals so that further work can be initiated to improve the quality of life in prediabetics that maybe drastically hampered due to easy fatigability in prediabetic individuals.